(untitled) - Gookin, Dan. (London, 2004)
The only book to focus exclusively on these two critical applications, Power Excel and Word teaches you how to harness their power and avoid their pitfalls in one compact volume. By following step-by-step tutorials, you'll discover how to work faster, easier, and smarter. Learn essential techniques you'll use every day
Keywords: Microsoft Excel (Computer file),Microsoft word (Computer file)